A high-impact polystyrene composition, a method for preparing the same and use thereof
Patent Information
- Application Number
- CN202611346060.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-09
AI Technical Summary
第一,本发明采用特定立构规整的乙烯-苯乙烯共聚物作为改性相,替代传统聚丁二烯橡胶增韧体系,与GPPS基体相容性优异,可在不牺牲材料抗冲击强度与刚性的前提下,大幅提升材料拉伸强度,彻底解决传统HIPS“增韧必降强”的技术难题,实现拉伸性能与抗冲击性能双向提升。
Smart Images

Figure SMS_3 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a high-impact polystyrene composition, its preparation method and application. Background Technology
[0002] Polystyrene (PS) is one of the most widely used general-purpose thermoplastic resins, possessing numerous advantages such as excellent light transmittance, high rigidity, good dimensional stability, excellent electrical insulation properties, good processing fluidity, ease of coloring and molding, and low production cost. It is widely used in many fields, including household appliance housings, food packaging, daily necessities, stationery and toys, electronic and electrical components, and architectural decoration, with a massive scale of industrial applications. However, general-purpose polystyrene (GPPS) has poor molecular chain flexibility, high brittleness, and extremely poor impact resistance. It is prone to cracking and chipping under external impact, greatly limiting its application in mid-to-high-end structural components, impact-resistant parts, and long-term service scenarios.
[0003] To overcome the insufficient toughness of general-purpose polystyrene, the industry widely employs rubber toughening modification technology to prepare high-impact polystyrene (HIPS). The mainstream process involves introducing rubber phases such as polybutadiene into the styrene polymerization system, forming an island structure through graft polymerization. Utilizing the stress concentration and crazing termination effect of the rubber particles, the impact resistance of the polystyrene matrix is significantly improved. Traditional HIPS effectively improves the brittleness of polystyrene while retaining its excellent processing performance and mechanical rigidity, and has become a core modified plastic material in the fields of home appliances, packaging, and daily necessities.
[0004] However, traditional HIPS preparation technology still suffers from many insurmountable technical defects. First, most current mainstream rubber toughening systems use single-component polybutadiene modification, resulting in a single polymerization reaction, limited interfacial compatibility between the rubber phase and the polystyrene matrix, insufficient toughening efficiency, and difficulty in simultaneously improving the tensile strength and impact strength of the material. This often leads to a "toughening but weakening" problem, failing to meet the demands of high-load and high-impact applications. Second, traditional HIPS polymerization products retain a large number of unreacted carbon-carbon double bonds in their molecular chains. These double bonds are highly reactive and easily undergo oxidation, chain breakage, and cross-linking aging reactions under the influence of light, high temperature, and oxygen. This results in yellowing, cracking, and mechanical property degradation after long-term use, leading to poor aging resistance, short service life, and unsuitability for harsh service environments such as outdoor applications, cold chain environments, and long-term powered household appliances.
[0005] In summary, existing technologies for preparing high-impact polystyrene (HIPS) generally suffer from limitations such as limited mechanical properties, poor strength-toughness balance, high double bond residue, weak aging resistance, and insufficient overall service performance. These shortcomings make it difficult to meet the demands of high-end home appliances, precision electronics, and high-end packaging for high-performance, long-life, and highly stable HIPS materials. Therefore, developing a novel high-impact polystyrene-based multi-component copolymer material that combines excellent tensile strength, high impact resistance, low reactive carbon-carbon double bond content, and excellent aging resistance has become a pressing technical problem for those skilled in the art. Summary of the Invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a high-impact polystyrene composition, its preparation method and application, which effectively improves the tensile strength and impact strength of polystyrene, solves the performance shortcomings of traditional products, and meets the application requirements of high-performance, long-life and high-stability HIPS materials in high-end home appliances, precision electronics, high-end packaging and other fields.
[0007] This invention provides a high-impact polystyrene composition, prepared from raw materials comprising the following components in parts by weight: 60-99 parts of polystyrene resin; 1-40 parts of ethylene-styrene copolymer; Antioxidant 0-1 part.
[0008] Preferably, in the ethylene-styrene copolymer, the molar content of styrene structural units is 25 mol% to 60 mol%; The number-average molecular weight of the ethylene-styrene copolymer is 50,000 to 500,000.
[0009] Preferably, the method for preparing the ethylene-styrene copolymer includes: Under anhydrous and oxygen-free conditions, ethylene and styrene are copolymerized in an organic solvent in the presence of a catalyst composition to obtain an ethylene-styrene copolymer. The catalyst composition consists of a rare earth catalyst and a co-catalyst.
[0010] Preferably, the rare earth catalyst has the structure shown in Formula I; The rare earth catalyst has the structure shown in Formula I; Formula I; In Formula I, Cp represents cyclopentadiene and its derivatives, indene and its derivatives, or fluorene and its derivatives; Q 1 and Q 2 Independently selected from monoanionic ligands; L is a neutral Lewis base, tetrahydrofuran, ethylene glycol dimethyl ether, pyridine, or a substituted pyridine. w is an integer between 0 and 2; Ln represents rare earth metal elements such as scandium, yttrium, neodymium, gadolinium, dysprosium, holmium, erbium, thulium, ytterbium, or lutetium; The cocatalyst is cocatalyst B, or is composed of cocatalyst A and cocatalyst B; cocatalyst A includes organoboron salts or fluoroborane compounds; cocatalyst B includes main group alkyl reagents. The copolymerization reaction is carried out in an inert solvent; The inert solvent includes at least one of pentane, methylcyclopentane, n-hexane, n-heptane, petroleum ether, No. 6 oil, cyclohexane, ethylbenzene, toluene, xylene, chlorobenzene, dichlorobenzene, bromobenzene, and dichloromethane; The copolymerization reaction is carried out under an ethylene pressure of 0.1~5.0 MPa, a polymerization temperature of 40~180℃, and a time of 0.5~10h.
[0011] Preferably, Cp is tetramethylcyclopentadiene, tetramethylphenylcyclopentadiene, pentamethylcyclopentadiene, pentaphenylcyclopentadiene, tetraphenylcyclopentadiene, pentaethylcyclopentadiene, tetramethyl(trimethylsilyl)cyclopentadiene, tetramethyl(triethylsilyl)cyclopentadiene, tetramethyl(triisopropylsilyl)cyclopentadiene, tetramethyl(phenyldimethylsilyl)cyclopentadiene, tetramethyl(diphenylmethylsilyl)cyclopentadiene, tetramethyl(triphenylsilyl)cyclopentadiene, tetramethyl(di ... 1,3-Di(trimethylsilyl)cyclopentadiene, trimethylsilylcyclopentadiene, trimethylsilylcyclopentadiene, triethylsilylcyclopentadiene, triisopropylsilylcyclopentadiene, benzylcyclopentadiene, diphenylmethanecyclopentadiene, 1,3-di(trimethylsilyl)cyclopentadiene, 1,3-di(trimethylsilyl)indene, 1,3-di(trimethylsilyl)-2-methylindene, 9-trimethylsilylfluorene, 9-triethylsilylfluorene, 9-triisopropylsilylfluorene, 9-benzylfluorene, 9-di Phenylmethane fluorene, 9-trimethylsilyl-2,7-di-tert-butylfluorene, 9-triethylsilyl-2,7-di-tert-butylfluorene, 9-triisopropylsilyl-2,7-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-2,7-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-2,7-di-tert-butylfluorene, 9-(triphenylsilyl)-2,7-di-tert-butylfluorene, 9-benzyl-2,7-di-tert-butylfluorene, 9-diphenylmethane-2,7-di-tert-butylfluorene 9-Trimethylsilyl-3,6-di-tert-butylfluorene, 9-Triethylsilyl-3,6-di-tert-butylfluorene, 9-Triisopropylsilyl-3,6-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-3,6-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-3,6-di-tert-butylfluorene, 9-(triphenylsilyl)-3,6-di-tert-butylfluorene, 9-benzyl-3,6-di-tert-butylfluorene, or 9-diphenylmalkyl-3,6-di-tert-butylfluorene; Q 1 and Q2 It is independently selected from alkyl, silyl, amino, silamido, aromatic amino, allyl, aryl, borohydride, tetramethylalumino, hydrogen, chlorine, bromine or iodine.
[0012] Preferably, in the rare earth catalyst having the structure shown in Formula I, Cp = C5Me4SiMe3, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4SiEt3, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4Si i Pr3, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4SiMe2Ph, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4Ph, Q 1 =Q 2 =CH2C6H4NMe2-2, Ln=Sc, L=THF, w=1; Or Cp = FluSiMe3, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp = FluSiMe2Ph, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=FluSiMePh2, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp = FluCH2Ph, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp = FluCHPh2, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp=2,7- t Bu2-FluCH2Ph, Q 1=Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp=2,7- t Bu2-FluCHPh2, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp=2,7- t Bu2-FluSiMe3, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp=2,7- t Bu2-FluSiEt3, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp=2,7- t Bu2-FluSiMe2Ph, Q 1 =Q 2 =CH2C6H5, Ln=Sc, L=THF, w=1.
[0013] Preferably, the co-catalyst A comprises [NHEt3][B(C6F5)4], [Ph3C][B(C6F5)4], [MeN(C 18 H 37 )2H][B(C6F5)4]、[MeN(C 16 H 35 [PhNMe2H][B(C6F5)4], [PhNMe2H][B(C6F5)4], or B(C6F5)3; The molar ratio of the co-catalyst A to the rare earth catalyst having the structure shown in Formula I is 0~2:1; The co-catalyst B comprises at least one of methylaluminoxane, dried aluminumoxane, modified aluminumoxane, trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-tert-butylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, ethylaluminum dihydrogen hydride, n-propylaluminum dihydrogen hydride, isobutylaluminum dihydrogen hydride, diethylzinc, diethylmagnesium, di-n-propylmagnesium, diisopropylmagnesium, dibutylmagnesium, and ethylbutylmagnesium. The molar ratio of the co-catalyst B to the rare earth catalyst having the structure shown in Formula I is 5~5000:1.
[0014] The present invention also provides a method for preparing the high-impact polystyrene composition described above, comprising the following steps: After mixing polystyrene resin, ethylene-styrene copolymer and antioxidant, the mixture is kneaded at 150~250℃ and extruded and granulated to obtain a high-impact polystyrene composition.
[0015] Preferably, the mixing is carried out in a mixer or a twin-screw extruder; the extrusion granulation is carried out in a twin-screw extruder. The rotor speed of the internal mixer is 10~200 r / min; the screw speed of the twin-screw extruder is 100~400 r / min; The mixing time is 5 to 120 minutes.
[0016] The present invention also provides the application of the high-impact polystyrene composition described above, or the high-impact polystyrene composition prepared by the method described above, in the preparation of automotive parts, housings and interior parts of household appliances, food and industrial packaging products, daily plastic products, plastic toys, and electronic and electrical accessories.
[0017] This invention aims to solve the technical problems of poor strength-toughness balance, weak aging resistance, and insufficient overall service performance of existing high-impact polystyrene (HIPS). It provides a novel high-impact polystyrene composition that optimizes the molecular chain and phase interface structure through a multi-component copolymerization modification system, effectively reducing the residual amount of double bonds in the polymer molecular chain. While retaining the excellent processing and molding properties of HIPS, it simultaneously and significantly improves the tensile strength and impact strength of the material, while also endowing it with excellent aging resistance. This addresses the performance shortcomings of traditional products and meets the application requirements of high-performance, long-life, and highly stable HIPS materials in high-end home appliances, precision electronics, and high-end packaging. Detailed Implementation
[0018] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] This invention provides a high-impact polystyrene composition, prepared from raw materials comprising the following components in parts by weight: 60-99 parts of polystyrene (GPPS) resin; 1-40 parts of ethylene-styrene copolymer; Antioxidant 0-1 part.
[0020] In some embodiments of the present invention, the polystyrene (GPPS) resin is present in parts by weight of 90, 99, 98, 95, 80, 60, and 80. The ethylene-styrene copolymer is present in parts by weight of 10, 1, 2, 5, 20, and 40. The antioxidant is present in parts by weight of 0.3, 0.1, and 0.5.
[0021] This invention abandons the traditional polybutadiene rubber toughening system and uses ethylene-styrene copolymer as the functional modifying phase. This copolymer has a similar structure to the polystyrene matrix and excellent interfacial compatibility. It can be uniformly dispersed in the polystyrene matrix, which can not only play a role in efficient toughening and absorbing impact energy, but also significantly improve the tensile strength and rigidity of the matrix, thus achieving synergistic optimization of strength and toughness.
[0022] In some embodiments of the present invention, the molar content of styrene structural units in the ethylene-styrene copolymer is 25 mol% to 60 mol%, for example, 25.0 mol%, 33.6 mol%, 42.9 mol%, 49.2 mol%, 53.4 mol%, 50.7 mol%, 56.2 mol%, 60.0 mol%, 41.6 mol%, and 58.7 mol%. The ethylene-styrene copolymer contains relatively long, continuous styrene structural unit segments, and these segments are predominantly syndiotactic and stereoregular. The molecular weight of the ethylene-styrene copolymer is 5.0 × 10⁻⁶. 4 ~50.0×10 4 g / mol, for example, 10.0 × 10 4 g / mol, 13.1×10 4 g / mol, 15.8×10 4 g / mol, 21.6×10 4 g / mol, 25.9×10 4 g / mol, 32.7×10 4 g / mol, 30.4×10 4 g / mol, 27.6×10 4 g / mol, 40.8×10 4 g / mol, 50.0×10 4 g / mol.
[0023] In some embodiments of the present invention, the molecular weight distribution (PDI) of the ethylene-styrene copolymer is 1.5 to 4.5, such as 1.95, 1.76, 2.31, 2.27, 2.58, 2.73, 2.52, 2.57, and 2.69.
[0024] The ethylene-styrene copolymer with the above-mentioned specific structure combines the flexible segments of polyethylene with the rigid and regular segments of syndiotactic polystyrene. The main chain of the molecule does not contain active carbon double bonds, which solves the problems of high double bond content, easy aging and yellowing, and mechanical property degradation of traditional modified systems from the molecular structure level. At the same time, the long continuous styrene segments can form good molecular compatibility with the GPPS matrix, greatly improve the interfacial bonding force, and significantly improve the tensile strength and impact resistance of the composite material.
[0025] In this invention, the ethylene-styrene copolymer is prepared by directional polymerization using a rare earth catalytic system. The specific preparation method is as follows: Under anhydrous and oxygen-free conditions, ethylene and styrene are copolymerized in an organic solvent in the presence of a catalyst composition to obtain an ethylene-styrene copolymer. The catalyst composition consists of a rare earth catalyst and a co-catalyst.
[0026] The rare earth catalyst has the structure shown in Formula I; Formula I; In Formula I, Cp represents cyclopentadiene and its derivatives, indene and its derivatives, or fluorene and its derivatives; Q 1 and Q 2 Independently selected from monoanionic ligands; L is a neutral Lewis base, tetrahydrofuran, ethylene glycol dimethyl ether, pyridine, or a substituted pyridine. w is an integer between 0 and 2; Ln represents rare earth metal elements such as scandium, yttrium, neodymium, gadolinium, dysprosium, holmium, erbium, thulium, ytterbium, or lutetium.
[0027] In some embodiments of the present invention, Cp is preferably tetramethylcyclopentadiene, tetramethylphenylcyclopentadiene, pentamethylcyclopentadiene, pentaphenylcyclopentadiene, tetraphenylcyclopentadiene, pentaethylcyclopentadiene, tetramethyl(trimethylsilyl)cyclopentadiene, tetramethyl(triethylsilyl)cyclopentadiene, tetramethyl(triisopropylsilyl)cyclopentadiene, tetramethyl(phenyldimethylsilyl)cyclopentadiene, tetramethyl(diphenylmethylsilyl)cyclopentadiene, tetramethyl(triphenylsilyl)cyclopentadiene, tetramethyl(diphenylmethane)cyclopentadiene, trimethylsilylcyclopentadiene, trimethylsilylcyclopentadiene, triethylsilylcyclopentadiene, triisopropylsilylcyclopentadiene, benzylcyclopentadiene, diphenylmethane cyclopentadiene, etc. Pentadiene, 1,3-di(trimethylsilyl)cyclopentadiene, 1,3-di(trimethylsilyl)indene, 1,3-di(trimethylsilyl)-2-methylindene, 9-trimethylsilylfluorene, 9-triethylsilylfluorene, 9-triisopropylsilylfluorene, 9-benzylfluorene, 9-diphenylmalkylfluorene, 9-trimethylsilyl-2,7-di-tert-butylfluorene, 9 -Triethylsilyl-2,7-di-tert-butylfluorene, 9-triisopropylsilyl-2,7-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-2,7-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-2,7-di-tert-butylfluorene, 9-(triphenylsilyl)-2,7-di-tert-butylfluorene, 9-benzyl-2,7-di-tert-butylfluorene, 9-di- Phenylenyl-2,7-di-tert-butylfluorene, 9-trimethylsilyl-3,6-di-tert-butylfluorene, 9-triethylsilyl-3,6-di-tert-butylfluorene, 9-triisopropylsilyl-3,6-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-3,6-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-3,6-di-tert-butylfluorene, 9-(triphenylsilyl)-3,6-di-tert-butylfluorene, 9-benzyl-3,6-di-tert-butylfluorene, or 9-diphenylmalkyl-3,6-di-tert-butylfluorene; preferably tetramethylcyclopentadiene, tetramethylphenylcyclopentadiene, pentamethylcyclopentadiene, tetramethyl(trimethylsilyl)cyclopentadiene, tetramethyl(triethylsilyl)cyclopentadiene, tetramethyl( 1,3-Di(trimethylsilyl)cyclopentadiene, tetramethyl(diphenylmethylsilyl)cyclopentadiene, tetramethyl(benzyl)cyclopentadiene, tetramethyl(diphenylmethane)cyclopentadiene, 1,3-di(trimethylsilyl)-2-methylindene, 9-trimethylsilylfluorene, 9-triethylsilylfluorene, 9-triisopropylsilylfluorene, 9-benzylfluorene, 9-diphenylmethane fluorene, 9-trimethylsilyl-2,7-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-2,7-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-2,7-di-tert-butylfluorene, 9-benzyl-2,7-di-tert-butylfluorene, 9-diphenylmethane-2,7-di-tert-butylfluorene, 9-trimethylsilyl-3,6-di-tert-butylfluorene;The most preferred are tetramethylphenylcyclopentadiene, tetramethyl(trimethylsilyl)cyclopentadiene, tetramethyl(triethylsilyl)cyclopentadiene, tetramethyl(phenyldimethylsilyl)cyclopentadiene, tetramethyl(benzyl)cyclopentadiene, 9-trimethylsilylfluorene, 9-triethylsilylfluorene, 9-triisopropylsilylfluorene, 9-benzylfluorene, 9-trimethylsilyl-2,7-di-tert-butylfluorene, or 9-benzyl-2,7-di-tert-butylfluorene.
[0028] In some embodiments of the present invention, Q 1 and Q 2 Independently selected from alkyl, silyl, amino, silamido, aromatic amino, allyl, aryl, borohydride, tetramethylaluminyl, hydrogen, chlorine, bromine, or iodine; preferably, Q 1 and Q 2 Independently selected from trimethylsilylmethylene, bis(trimethylsilylmethethylene), allyl, 2-methylallyl, 1,3-ditrimethylsilylallyl, hexamethylsilamido, tetramethylsilamido, methyl, benzyl, 4-methylbenzyl, 2-(N,N-dimethylamino)benzyl, 2-N,N'-dimethylbenzyl, tetramethylaluminyl, borohydride, hydrogen, chlorine, or bromine; more preferably, Q 1 and Q 2 Independently selected from trimethylsilylmethylene, allyl, 2-methylallyl, hexamethylsilamido, tetramethylsilamido, benzyl, 4-methylbenzyl, 2-(N,N-dimethylamino)benzyl, 2-N,N'-dimethylbenzyl, tetramethylaluminyl, or chlorine; most preferably, Q 1 and Q 2 It is independently selected from trimethylsilylmethylene, allyl, 2-methylallyl, tetramethylsilamido, benzyl, 4-methylbenzyl, 2-(N,N-dimethylamino)benzyl or 2-N,N'-dimethylbenzyl.
[0029] In some embodiments of the present invention, in the rare earth catalyst having the structure shown in Formula I, Cp = C5Me4SiMe3 (tetramethyltrimethylsilylcyclopentadiene), Q 1 =Q 2 =CH2SiMe3 (trimethylsilylmethylene), Ln=Sc, L=THF, w=1, denoted as complex 1.
[0030] In some embodiments of the present invention, in the rare earth catalyst having the structure shown in Formula I, Cp = C5Me4SiEt3 (tetramethyltriethylsilylcyclopentadiene), Q 1 =Q 2 =CH2SiMe3 (trimethylsilylmethylene), Ln=Sc, L=THF, w=1, denoted as complex 2.
[0031] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=C5Me4Si i Pr3 (tetramethyltriisopropylsilylcyclopentadiene), Q 1 =Q 2 =CH2SiMe3 (trimethylsilylmethylene), Ln=Sc, L=THF, w=1, which is designated as complex 3.
[0032] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=C5Me4SiMe2Ph (tetramethyldimethylphenylsilylcyclopentadiene), Q 1 =Q 2 =CH2SiMe3 (trimethylsilylmethylene), Ln=Sc, L=THF, w=1, which is designated as complex 4.
[0033] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=C5Me4Ph (tetramethylphenylcyclopentadiene), Q 1 =Q 2 =CH2C6H4NMe2-2 (2-(N,N-dimethylamino)benzyl), Ln=Sc, L=THF, w=1, which is designated as complex 5.
[0034] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=FluSiMe3 (Flu=fluorene), Q 1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 6.
[0035] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=FluSiMe2Ph (Flu=fluorene, Ph=phenyl), Q 1 =Q 2 =CH2SiMe3 (trimethylsilylmethylene), Ln=Sc, L=THF, w=1, which is designated as complex 7.
[0036] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=FluSiMePh2 (Flu=fluorene, Ph=phenyl), Q 1 =Q 2 =CH2SiMe3 (trimethylsilylmethylene), Ln=Sc, L=THF, w=1, which is designated as complex 8.
[0037] In some embodiments of the present invention, in the rare earth catalyst having the structure represented by formula I, Cp=FluCH2Ph (Flu=fluorene, Ph=phenyl), Q1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 9.
[0038] In some embodiments of the present invention, in the rare-earth catalyst having the structure represented by formula I, Cp=FluCHPh2 (Flu=fluorene, Ph=phenyl), Q 1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 10.
[0039] In some embodiments of the present invention, in the rare-earth catalyst having the structure represented by formula I, Cp=2,7- t Bu2-FluCH2Ph (Flu=fluorene, Ph=phenyl), Q 1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 11.
[0040] In some embodiments of the present invention, in the rare-earth catalyst having the structure represented by formula I, Cp=2,7- t Bu2-FluCHPh2 (Flu=fluorene, Ph=phenyl), Q 1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 12.
[0041] In some embodiments of the present invention, in the rare-earth catalyst having the structure represented by formula I, Cp=2,7- t Bu2-FluSiMe3 (Flu=fluorene), Q 1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 13.
[0042] In some embodiments of the present invention, in the rare-earth catalyst having the structure represented by formula I, Cp=2,7- t Bu2-FluSiEt3 (Flu=fluorene), Q 1 =Q 2 =CH2C6H4Me-4 (4-methylbenzyl), Ln=Sc, L=THF, w=1, which is designated as complex 14.
[0043] In some embodiments of the present invention, in the rare-earth catalyst having the structure represented by formula I, Cp=2,7- tBu2-FluSiMe2Ph (Flu = fluorene, Ph = phenyl), Q 1 =Q 2 =CH2C6H5 (benzyl), Ln=Sc, L=THF, w=1, denoted as complex 15.
[0044] The present invention does not impose any special restrictions on the preparation method of the rare earth catalyst, which can be synthesized according to the methods described in the literature (Polym. Chem. 2018, 9, 4476-4482; Organometallics 2013, 32, 1445-1458).
[0045] In some embodiments of the present invention, the cocatalyst is cocatalyst B, or is composed of cocatalyst A and cocatalyst B; cocatalyst A is an organoboron salt or a fluoroborane compound; and cocatalyst B is a group alkyl reagent.
[0046] In some embodiments of the present invention, the co-catalyst A is a boron-containing anion [B(C6F5)4]. - Specifically, the compounds can be [NHEt3][B(C6F5)4], [Ph3C][B(C6F5)4], [MeN(C 18 H 37 )2H][B(C6F5)4]、[MeN(C 16 H 35 [PhNMe2H][B(C6F5)4], [PhNMe2H][B(C6F5)4], or B(C6F5)3. The molar ratio of the cocatalyst A to the rare earth catalyst having the structure shown in Formula I is 0 to 2:1, for example, 1:1. In particular, when the cocatalyst B is sufficient aluminoxane, the amount of cocatalyst A can be 0.
[0047] In some embodiments of the present invention, the co-catalyst B is at least one selected from alkylaluminoxane, alkylaluminum, haloalkylaluminum, alkylmagnesium, and alkylzinc. Specifically, it can be methylaluminoxane (MAO), dried aluminumoxane (DMAO), modified aluminumoxane (MMAO, such as modified methylaluminoxane, modified ethylaluminoxane), trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, or triisobutylaluminum (Al). iBu3), at least one of the following: tri-tert-butylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, ethylaluminum dihydrogen hydride, n-propylaluminum dihydrogen hydride, isobutylaluminum dihydrogen hydride, diethylzinc, diethylmagnesium, di-n-propylmagnesium, diisopropylmagnesium, dibutylmagnesium, and ethylbutylmagnesium. The molar ratio of the co-catalyst B to the rare earth catalyst having the structure shown in Formula I is 5~5000:1, for example, 40:1, 50:1, 10:1, 20:1, 30:1, 40:1, 500:1, 1000:1, 2000:1, 3000:1, 4000:1, or 5000:1.
[0048] In some embodiments of the present invention, the molar ratio of the rare earth catalyst having the structure shown in Formula I to styrene is 1:1000~500000.
[0049] In some embodiments of the present invention, the copolymerization reaction is carried out in an inert solvent. The inert solvent is at least one selected from pentane, methylcyclopentane, n-hexane, n-heptane, petroleum ether, No. 6 oil, cyclohexane, ethylbenzene, toluene, xylene, chlorobenzene, dichlorobenzene, bromobenzene, and dichloromethane.
[0050] In some embodiments of the present invention, the ethylene pressure of the copolymerization reaction is 0.1~5.0 MPa, for example 0.1 MPa; the polymerization temperature is 40~180℃, for example 60℃; and the time is 0.5~10 h, for example 0.5 h.
[0051] In some embodiments of the present invention, the copolymerization reaction is followed by terminating the reaction with ethanol acidified with hydrochloric acid. The pH value of the ethanol acidified with hydrochloric acid is 3.
[0052] In some embodiments of the present invention, the antioxidant is antioxidant 1010.
[0053] The present invention also provides a method for preparing the high-impact polystyrene composition described above, comprising the following steps: After mixing polystyrene (GPPS) resin, ethylene-styrene copolymer and antioxidant, the mixture is kneaded at 150~250℃ and extruded and granulated to obtain a high-impact polystyrene composition.
[0054] In some embodiments of the present invention, the mixing is carried out in a mixer or a twin-screw extruder; the extrusion granulation is carried out in a twin-screw extruder.
[0055] The specific mixing temperatures are 190℃, 150℃, 170℃, 210℃, 230℃, 250℃, and 200℃.
[0056] The rotor speed of the internal mixer is 10~200 r / min, such as 60 r / min or 100 r / min; the mixing time using the internal mixer is 5~120 min, such as 5 min, 20 min or 15 min.
[0057] The screw speed of the twin-screw extruder is 100~400 r / min, for example, 300 r / min.
[0058] This invention also provides the application of the high-impact polystyrene composition described above, or the high-impact polystyrene composition prepared by the method described above, in the preparation of automotive parts, household appliance housings and interior parts, food and industrial packaging products, daily-use plastic products, plastic toys, and electronic and electrical accessories. It has a wide range of applications and broad market prospects.
[0059] The present invention does not impose any special restrictions on the source of the raw materials used above, and they can be commercially available.
[0060] Compared with the prior art, the present invention has the following significant advantages: First, this invention uses a specific stereoregular ethylene-styrene copolymer as a modified phase to replace the traditional polybutadiene rubber toughening system. It has excellent compatibility with the GPPS matrix and can significantly improve the tensile strength of the material without sacrificing its impact strength and rigidity. This completely solves the technical problem of "toughening inevitably reduces strength" in traditional HIPS and achieves a two-way improvement in tensile properties and impact resistance.
[0061] Secondly, this invention regulates the molecular structure of copolymers through rare earth directional polymerization, resulting in ethylene-styrene copolymers with extremely low double bond residues. This improves the aging resistance of the material from the molecular level, effectively improving the defects of traditional HIPS such as yellowing, cracking, and mechanical degradation after long-term use, and significantly extending the service life of the products.
[0062] Third, this invention does not require the addition of a large amount of anti-aging and toughening additives, and only requires a small amount or even no antioxidants, thus avoiding the problems of migration, precipitation, pollution, and impact on the appearance and environmental friendliness of traditional additives, resulting in higher material stability and safety.
[0063] Fourth, the raw material ratio of this invention is simple, the preparation process is conventional and controllable, it is compatible with a variety of industrial processing equipment, has high production efficiency and controllable cost, and can be applied on a large scale. The high-performance HIPS material prepared can meet the needs of high-end fields such as high-end home appliances, precision electronics, and automotive interiors.
[0064] To further illustrate the present invention, the following detailed description of a high-impact polystyrene composition, its preparation method, and its application, in conjunction with embodiments, is provided by the present invention, but should not be construed as limiting the scope of protection of the present invention.
[0065] The rare earth catalyst used in the embodiments of the present invention can be synthesized according to the method described in the literature (Polym. Chem. 2018, 9, 4476-4482; Organometallics 2013, 32, 1445-1458) to obtain complex 7.
[0066] Example 1
[0067] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 20.4 g, 0.2 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (0.4 mmol) and cyclohexane (600 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.7 MPa. The copolymerization reaction was carried out in an oil bath at 60 °C for 2 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 16.7 g of ethylene-styrene copolymer. The copolymer contained 25.0 mol% styrene structural units, with a molecular weight Mn = 10.0 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=1.95, melting temperature T m =124℃.
[0068] Example 2
[0069] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.04 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (0.4 mmol) and cyclohexane (60 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.1 MPa. The copolymerization reaction was carried out in an oil bath at 40 °C for 0.5 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 4.18 g of ethylene-styrene copolymer. The copolymer contained 33.6 mol% styrene structural units, with a molecular weight Mn = 13.1 × 10⁻⁶. 4g / mol, molecular weight distribution PDI=1.76, melting temperature T m =118℃, T m = 242℃.
[0070] Example 3
[0071] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.10 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (0.6 mmol) and cyclohexane (100 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.4 MPa. The copolymerization reaction was carried out in an oil bath at 60 °C for 1 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 19.3 g of ethylene-styrene copolymer. The copolymer contained 42.9 mol% styrene structural units, with a molecular weight Mn = 15.8 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.31, melting temperature Tm=121℃, Tm=234℃.
[0072] Example 4
[0073] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.20 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (0.7 mmol) and cyclohexane (300 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.5 MPa. The copolymerization reaction was carried out in an oil bath at 70 °C for 3 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 20.5 g of ethylene-styrene copolymer. The copolymer contained 49.2 mol% styrene structural units, with a molecular weight Mn = 21.6 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.27, melting temperature Tm=125℃, Tm=231℃.
[0074] Example 5
[0075] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.40 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (0.8 mmol) and cyclohexane (400 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.6 MPa. The copolymerization reaction was carried out in an oil bath at 70 °C for 3 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 39.7 g of ethylene-styrene copolymer. The copolymer contained 53.4 mol% styrene structural units, with a molecular weight Mn = 25.9 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.58, melting temperature Tm=127℃, Tm=236℃.
[0076] Example 6
[0077] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.50 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (0.8 mmol) and cyclohexane (600 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.8 MPa. The copolymerization reaction was carried out in an oil bath at 80 °C for 4 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 49.0 g of ethylene-styrene copolymer. The copolymer contained 50.7 mol% styrene structural units, with a molecular weight Mn = 32.7 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.73, melting temperature Tm=117℃, Tm=237℃.
[0078] Example 7
[0079] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.80 mol) and triisobutylaluminum (Al2O3). iA mixed solution of Bu3 (1.0 mmol) and cyclohexane (1000 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 1.0 MPa. The copolymerization reaction was carried out in an oil bath at 70 °C for 5 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 67.8 g of ethylene-styrene copolymer. The copolymer contained 56.2 mol% styrene structural units, with a molecular weight Mn = 30.4 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.52, melting temperature Tm=127℃, Tm=221℃.
[0080] Example 8
[0081] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 0.90 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (1.0 mmol) and cyclohexane (1200 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 0.6 MPa. The copolymerization reaction was carried out in an oil bath at 75 °C for 4 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 71.4 g of ethylene-styrene copolymer. The copolymer contained 60.0 mol% styrene structural units, with a molecular weight Mn = 27.6 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.57, melting temperature Tm=114℃, Tm=252℃.
[0082] Example 9
[0083] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 1.0 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (1.0 mmol) and cyclohexane (1200 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 5.0 MPa. The copolymerization reaction was carried out in an oil bath at 70 °C for 6 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 86.7 g of ethylene-styrene copolymer. The copolymer contained 41.6 mol% styrene structural units, with a molecular weight Mn = 40.8 × 10⁻⁶. 4g / mol, molecular weight distribution PDI=2.69, melting temperature Tm=120℃, Tm=224℃.
[0084] Example 10
[0085] Under anhydrous and oxygen-free conditions, 10 μmol of complex 7 and 10 μmol of [Ph3C][B(C6F5)4] were mixed in 2 mL of toluene solution to obtain a rare earth metal catalyst composition solution. This rare earth metal catalyst composition solution was then injected into a container containing styrene monomer (first monomer, 1.0 mol) and triisobutylaluminum (Al2O3). i A mixed solution of Bu3 (1.0 mmol) and cyclohexane (1500 mL) was prepared, followed by the introduction of ethylene gas (second monomer) at 1.5 MPa. The copolymerization reaction was carried out in an oil bath at 70 °C for 10 h. The reaction was then terminated by adding hydrochloric acid-acidified ethanol (pH 3), yielding 104.5 g of ethylene-styrene copolymer. The copolymer contained 58.7 mol% styrene structural units, with a molecular weight Mn = 50.0 × 10⁻⁶. 4 g / mol, molecular weight distribution PDI=2.73, melting temperature Tm=124℃, Tm=232℃.
[0086] The performance parameters of the copolymers prepared in Examples 1-10 are shown in Table 1.
[0087] Table 1 Performance parameters of the copolymers prepared in Examples 1-10
[0088] Application Example 1
[0089] Preparation of polystyrene compositions: Take 90 parts by weight of polystyrene (GPPS), 10 parts by weight of the ethylene-styrene copolymer prepared in Example 2, and 0.3 parts by weight of antioxidant 1010. After mixing evenly, put the mixture into a twin-screw extruder (screw speed of 300 r / min), knead at 190°C, and extrude and granulate to prepare a polystyrene composition with uniform composition.
[0090] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 19.3 kJ / m. 2 The tensile strength is 71.3 MPa and the elongation at break is 12.9%.
[0091] Application Example 2
[0092] Replace the mixing temperature in Application Example 1 with 150°C.
[0093] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0094] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 17.9 kJ / m. 2 The tensile strength is 69.5 MPa and the elongation at break is 10.9%.
[0095] Application Example 3
[0096] Replace the mixing temperature in Application Example 1 with 170°C.
[0097] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0098] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The molded specimens were subjected to performance testing, and the unnotched cantilever beam impact strength of the material was measured to be 18.6 kJ / m. 2 The tensile strength is 70.6 MPa and the elongation at break is 11.3%.
[0099] Application Example 4
[0100] Replace the mixing temperature in Application Example 1 with 210℃.
[0101] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0102] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The molded specimens were subjected to performance testing, and the unnotched cantilever beam impact strength of the material was measured to be 19.5 kJ / m. 2 The tensile strength is 70.8 MPa and the elongation at break is 11.9%.
[0103] Application Example 5
[0104] Replace the mixing temperature in Application Example 1 with 230°C.
[0105] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0106] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The molded specimens were subjected to performance testing, and the unnotched cantilever beam impact strength of the material was measured to be 17.8 kJ / m. 2 The tensile strength is 70.2 MPa and the elongation at break is 11.6%.
[0107] Application Example 6
[0108] Replace the mixing temperature in Application Example 1 with 250°C.
[0109] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0110] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The molded specimens were subjected to performance testing, and the unnotched cantilever beam impact strength of the material was measured to be 17.6 kJ / m. 2 The tensile strength is 68.2 MPa and the elongation at break is 10.4%.
[0111] Application Example 7
[0112] The difference from application example 1 is: The mixing process was carried out using an internal mixer at a temperature of 200℃, a rotor speed of 60 r / min, and a mixing time of 5 min. Extrusion granulation was performed using a twin-screw extruder (screw speed of 300 r / min).
[0113] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0114] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 18.1 kJ / m. 2 The tensile strength is 70.5 MPa and the elongation at break is 11.4%.
[0115] Application Example 8
[0116] Replace the internal mixer rotor speed in Application Example 7 with 100 r / min and the mixing time with 20 min.
[0117] The remaining steps are the same as in Application Example 1, and a polystyrene composition with uniform composition is prepared.
[0118] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 19.1 kJ / m. 2 The tensile strength is 70.9 MPa and the elongation at break is 11.7%.
[0119] Application Example 9
[0120] Replace the amount of antioxidant 1010 in Application Example 7 with 0.1 parts by weight.
[0121] The remaining steps are the same as in Application Example 7, and a polystyrene composition with uniform composition is prepared.
[0122] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. Performance tests were performed on the molded specimens, and the unnotched cantilever beam impact strength of the material was measured to be 18.8 kJ / m. 2 The tensile strength is 70.7 MPa and the elongation at break is 11.4%.
[0123] Application Example 10
[0124] Replace the amount of antioxidant 1010 in Application Example 7 with 0.5 parts by weight.
[0125] The remaining steps are the same as in Application Example 7, and a polystyrene composition with uniform composition is prepared.
[0126] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 19.2 kJ / m. 2 The tensile strength is 71.0 MPa and the elongation at break is 11.8%.
[0127] Application Example 11
[0128] The amount of polystyrene (GPPS) in Application Example 7 was replaced with 99 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 2 was replaced with 1 part by weight.
[0129] The remaining steps are the same as in Application Example 7, and a polystyrene composition with uniform composition is prepared.
[0130] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 9.2 kJ / m.2 The tensile strength is 62.1 MPa and the elongation at break is 10.2%.
[0131] Application Example 12
[0132] The amount of polystyrene (GPPS) in Application Example 7 was replaced with 98 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 2 was replaced with 2 parts by weight.
[0133] The remaining steps are the same as in Application Example 7, and a polystyrene composition with uniform composition is prepared.
[0134] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance and tensile performance testing. Performance tests were performed on the molded specimens, and the unnotched cantilever beam impact strength of the material was measured to be 10.7 kJ / m. 2 The tensile strength is 65.6 MPa and the elongation at break is 10.3%.
[0135] Application Example 13
[0136] The amount of polystyrene (GPPS) in Application Example 7 was replaced with 95 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 2 was replaced with 5 parts by weight.
[0137] The remaining steps are the same as in Application Example 7, and a polystyrene composition with uniform composition is prepared.
[0138] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 11.9 kJ / m. 2 The tensile strength is 69.1 MPa and the elongation at break is 12.5%.
[0139] Application Example 14
[0140] Preparation of polystyrene compositions: Take 90 parts by weight of polystyrene (GPPS), 10 parts by weight of the ethylene-styrene copolymer prepared in Example 6, and 0.3 parts by weight of antioxidant 1010. After mixing evenly, put it into an internal mixer. The mixing temperature is 190°C, the rotor speed of the internal mixer is 60 r / min, and the mixing time is 15 min. Then, use a twin-screw extruder (screw speed is 300 r / min) to extrude and granulate to prepare a polystyrene composition with uniform composition.
[0141] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 44.6 kJ / m. 2 The tensile strength is 71.5 MPa and the elongation at break is 12.8%.
[0142] Application Example 15
[0143] The amount of polystyrene (GPPS) in Application Example 14 was replaced with 80 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 6 was replaced with 20 parts by weight.
[0144] The remaining steps are the same as in Application Example 14, and a polystyrene composition with uniform composition is prepared.
[0145] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 47.5 kJ / m. 2 The tensile strength is 71.2 MPa and the elongation at break is 13.4%.
[0146] Application Example 16
[0147] The amount of polystyrene (GPPS) in Application Example 14 was replaced with 99 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 6 was replaced with 1 part by weight.
[0148] The remaining steps are the same as in Application Example 14, and a polystyrene composition with uniform composition is prepared.
[0149] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 23.0 kJ / m. 2 The tensile strength is 64.6 MPa and the elongation at break is 10.4%.
[0150] Application Example 17
[0151] The amount of polystyrene (GPPS) in Application Example 14 was replaced with 98 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 6 was replaced with 2 parts by weight.
[0152] The remaining steps are the same as in Application Example 14, and a polystyrene composition with uniform composition is prepared.
[0153] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 26.2 kJ / m. 2 The tensile strength is 67.9 MPa and the elongation at break is 11.7%.
[0154] Application Example 18
[0155] The amount of polystyrene (GPPS) in Application Example 14 was replaced with 95 parts by weight, and the amount of ethylene-styrene copolymer prepared in Example 6 was replaced with 5 parts by weight.
[0156] The remaining steps are the same as in Application Example 14, and a polystyrene composition with uniform composition is prepared.
[0157] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The molded specimens were subjected to performance testing, and the unnotched cantilever beam impact strength of the material was measured to be 39.0 kJ / m. 2 The tensile strength is 70.1 MPa and the elongation at break is 12.3%.
[0158] Application Example 19
[0159] The ethylene-styrene copolymer prepared in Example 6 of Application Example 14 was replaced with the ethylene-styrene copolymer prepared in Example 9.
[0160] The remaining steps are the same as in Application Example 14, and a polystyrene composition with uniform composition is prepared.
[0161] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance and tensile performance testing. The molded specimens were subjected to performance testing, and the unnotched cantilever beam impact strength of the material was measured to be 15.8 kJ / m. 2 The tensile strength is 50.8 MPa and the elongation at break is 8.6%.
[0162] Application Example 20
[0163] The ethylene-styrene copolymer prepared in Example 6 of Application Example 14 was replaced with the ethylene-styrene copolymer prepared in Example 2.
[0164] The remaining steps are the same as in Application Example 14, and a polystyrene composition with uniform composition is prepared.
[0165] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 21.6 kJ / m. 2 The tensile strength is 67.9 MPa and the elongation at break is 21.3%.
[0166] Application Example 21
[0167] Preparation of polystyrene compositions: Take 60 parts by weight of polystyrene (GPPS) and 40 parts by weight of the ethylene-styrene copolymer prepared in Example 1, mix them evenly, and put them into a mixer. The mixing temperature is 190°C, the rotor speed of the mixer is 60 r / min, and the mixing time is 15 min. Then, extrusion granulation is carried out using a twin-screw extruder (screw speed is 300 r / min) to prepare a polystyrene composition with uniform composition.
[0168] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 21.6 kJ / m. 2 The tensile strength is 27.2 MPa and the elongation at break is 31.7%.
[0169] Application Example 22
[0170] Preparation of polystyrene compositions: Take 80 parts by weight of polystyrene (GPPS), 20 parts by weight of the ethylene-styrene copolymer prepared in Example 5, and 0.3 parts by weight of antioxidant 1010. After mixing evenly, put it into a mixer. The mixing temperature is 190°C, the rotor speed of the mixer is 60 r / min, and the mixing time is 15 min. Then, use a twin-screw extruder (screw speed is 300 r / min) to extrude and granulate to prepare a polystyrene composition with uniform composition.
[0171] The obtained polystyrene composition was placed in an injection molding machine and injection molded at 230℃ to prepare standard specimens for impact performance testing and tensile performance testing. The performance of the molded specimens was tested, and the unnotched cantilever beam impact strength of the material was measured to be 42.7 kJ / m. 2 The tensile strength is 70.8 MPa and the elongation at break is 11.7%.
[0172] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-impact polystyrene composition, characterized in that, It is prepared from raw materials comprising the following components in parts by weight: 60-99 parts of polystyrene resin; 1-40 parts of ethylene-styrene copolymer; Antioxidant 0-1 part.
2. The high-impact polystyrene composition according to claim 1, characterized in that, In the ethylene-styrene copolymer, the molar content of styrene structural units is 25 mol%~60 mol%; The number-average molecular weight of the ethylene-styrene copolymer is 50,000 to 500,000.
3. The high-impact polystyrene composition according to claim 1, characterized in that, The method for preparing the ethylene-styrene copolymer includes: Under anhydrous and oxygen-free conditions, ethylene and styrene are copolymerized in an organic solvent in the presence of a catalyst composition to obtain an ethylene-styrene copolymer. The catalyst composition consists of a rare earth catalyst and a co-catalyst.
4. The high-impact polystyrene composition according to claim 3, characterized in that, The rare earth catalyst has the structure shown in Formula I; The rare earth catalyst has the structure shown in Formula I; Equation I; In Formula I, Cp represents cyclopentadiene and its derivatives, indene and its derivatives, or fluorene and its derivatives; Q 1 and Q 2 Independently selected from monoanionic ligands; L is a neutral Lewis base, tetrahydrofuran, ethylene glycol dimethyl ether, pyridine, or a substituted pyridine. w is an integer between 0 and 2; Ln represents rare earth metal elements such as scandium, yttrium, neodymium, gadolinium, dysprosium, holmium, erbium, thulium, ytterbium, or lutetium; The cocatalyst is cocatalyst B, or is composed of cocatalyst A and cocatalyst B; cocatalyst A includes organoboron salts or fluoroborane compounds; cocatalyst B includes main group alkyl reagents. The copolymerization reaction is carried out in an inert solvent; The inert solvent includes at least one of pentane, methylcyclopentane, n-hexane, n-heptane, petroleum ether, No. 6 oil, cyclohexane, ethylbenzene, toluene, xylene, chlorobenzene, dichlorobenzene, bromobenzene, and dichloromethane; The copolymerization reaction is carried out under an ethylene pressure of 0.1~5.0 MPa, a polymerization temperature of 40~180℃, and a time of 0.5~10 h.
5. The high-impact polystyrene composition according to claim 4, characterized in that, Cp represents tetramethylcyclopentadiene, tetramethylphenylcyclopentadiene, pentamethylcyclopentadiene, pentaphenylcyclopentadiene, tetraphenylcyclopentadiene, pentaethylcyclopentadiene, tetramethyl(trimethylsilyl)cyclopentadiene, tetramethyl(triethylsilyl)cyclopentadiene, tetramethyl(triisopropylsilyl)cyclopentadiene, tetramethyl(phenyldimethylsilyl)cyclopentadiene, tetramethyl(diphenylmethylsilyl)cyclopentadiene, tetramethyl(triphenylsilyl)cyclopentadiene, tetramethyl(diphenylmethylsilyl)cyclopentadiene, and tetramethyl(diphenylsilyl)cyclopentadiene. Alkyl)cyclopentadiene, trimethylsilylcyclopentadiene, trimethylsilylcyclopentadiene, triethylsilylcyclopentadiene, triisopropylsilylcyclopentadiene, benzylcyclopentadiene, diphenylmethanecyclopentadiene, 1,3-di(trimethylsilyl)cyclopentadiene, 1,3-di(trimethylsilyl)indene, 1,3-di(trimethylsilyl)-2-methylindene, 9-trimethylsilylfluorene, 9-triethylsilylfluorene, 9-triisopropylsilylfluorene, 9-benzylfluorene, 9-diphenyl Methylfluorene, 9-trimethylsilyl-2,7-di-tert-butylfluorene, 9-triethylsilyl-2,7-di-tert-butylfluorene, 9-triisopropylsilyl-2,7-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-2,7-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-2,7-di-tert-butylfluorene, 9-(triphenylsilyl)-2,7-di-tert-butylfluorene, 9-benzyl-2,7-di-tert-butylfluorene, 9-diphenylmalkyl-2,7-di-tert-butyl Fluorene, 9-trimethylsilyl-3,6-di-tert-butylfluorene, 9-triethylsilyl-3,6-di-tert-butylfluorene, 9-triisopropylsilyl-3,6-di-tert-butylfluorene, 9-(dimethylphenylsilyl)-3,6-di-tert-butylfluorene, 9-(diphenylmethylsilyl)-3,6-di-tert-butylfluorene, 9-(triphenylsilyl)-3,6-di-tert-butylfluorene, 9-benzyl-3,6-di-tert-butylfluorene or 9-diphenylmalkyl-3,6-di-tert-butylfluorene; Q 1 and Q 2 It is independently selected from alkyl, silyl, amino, silamido, aromatic amino, allyl, aryl, borohydride, tetramethylalumino, hydrogen, chlorine, bromine or iodine.
6. The high-impact polystyrene composition according to claim 4, characterized in that, In rare earth catalysts with the structure shown in Formula I, Cp = C5Me4SiMe3, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4SiEt3, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4Si i Pr3, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4SiMe2Ph, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; Or Cp=C5Me4Ph, Q 1 =Q 2 =CH2C6H4NMe2-2, Ln=Sc, L=THF, w=1; or Cp=FluSiMe3, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; Or Cp = FluSiMe2Ph, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; or Cp=FluSiMePh2, Q 1 =Q 2 =CH2SiMe3, Ln=Sc, L=THF, w=1; or Cp=FluCH2Ph, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; or Cp=FluCHPh2, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; or Cp=2,7- t Bu2-FluCH2Ph, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; or Cp=2,7- t Bu2-FluCHPh2, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; or Cp=2,7- t Bu₂-FluSiMe₃, Q 1 =Q 2 =CH₂C₆H₄Me-4, Ln=Sc, L=THF, w=1; or Cp=2,7- t Bu2-FluSiEt3, Q 1 =Q 2 =CH2C6H4Me-4, Ln=Sc, L=THF, w=1; or Cp=2,7- t Bu2-FluSiMe2Ph, Q 1 = Q 2 = CH2C6H5, Ln=Sc, L=THF, w=1.
7. The high-impact polystyrene composition according to claim 4, characterized in that, The cocatalyst A includes [NHEt3][B(C6F5)4], [Ph3C][B(C6F5)4], [MeN(C], [NHEt3 ... 18 H 37 )2H][B(C6F5)4]、[MeN(C 16 H 35 [PhNMe2H][B(C6F5)4], [PhNMe2H][B(C6F5)4], or B(C6F5)3; The molar ratio of the co-catalyst A to the rare earth catalyst having the structure shown in Formula I is 0~2:1; The co-catalyst B comprises at least one of methylaluminoxane, dried aluminumoxane, modified aluminumoxane, trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-tert-butylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, ethylaluminum dihydrogen hydride, n-propylaluminum dihydrogen hydride, isobutylaluminum dihydrogen hydride, diethylzinc, diethylmagnesium, di-n-propylmagnesium, diisopropylmagnesium, dibutylmagnesium, and ethylbutylmagnesium. The molar ratio of the co-catalyst B to the rare earth catalyst having the structure shown in Formula I is 5~5000:
1.
8. A method for preparing the high-impact polystyrene composition according to any one of claims 1 to 7, comprising the following steps: After mixing polystyrene resin, ethylene-styrene copolymer and antioxidant, the mixture is kneaded at 150~250℃ and extruded and granulated to obtain a high-impact polystyrene composition.
9. The preparation method according to claim 8, characterized in that, The mixing is carried out in an internal mixer or a twin-screw extruder; the extrusion granulation is carried out in a twin-screw extruder; The rotor speed of the internal mixer is 10~200 r / min; the screw speed of the twin-screw extruder is 100~400 r / min; The mixing time is 5 to 120 minutes.
10. The use of the high-impact polystyrene composition according to any one of claims 1 to 7, or the high-impact polystyrene composition prepared by the preparation method according to any one of claims 8 to 9, in the preparation of automotive parts, housings and interior parts of household appliances, food and industrial packaging products, daily plastic products, plastic toys, and electronic and electrical accessories.